Eye Movements and Problem Solving - Grant, Elizabeth R.; Spivey, Michael J. (Psychological Science, 2003)
Overt visual attention during diagram-based problem solving, as measured by eye movements, has been used in numerous studies to reveal critical aspects of the problem-solving process that traditional measures like solution time and accuracy cannot address. In Experiment 1, we used this methodology to show that particular fixation patterns correlate with success in solving the tumor-and-lasers radiation problem. Given this correlation between attention to a particular diagram feature and problem-solving insight, we investigated participants' cognitive sensitivity to perceptual changes in that diagram feature. In Experiment 2, we found that perceptually highlighting the critical diagram component, identified in Experiment 1, significantly increased the frequency of correct solutions. Taking a situated perspective on cognition, we suggest that environmentally controlled perceptual properties can guide attention and eye movements in ways that assist in developing problem-solving insights that dramatically improve reasoning.